Do We Need a Negative Culture? Examining the Role of Final Debridement Cultures in Microsurgical Limb Salvage: Recommendations from Our 13-Year Experience - Rohrich, Rachel N.; Carreras, Joshua P.; Sharma, Sahil; Lin, Ryan P.; Ferdousian, Sami; Currin, Meghan E.; Youn, Richard C.; Attinger, Christopher E.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2025)
Lower extremity free tissue transfer (LE FTT) expands limb salvage options for patients with chronic wounds. Infected wounds require serial debridement to optimize the wound bed before reconstruction, but the role of qualitative microbiological cultures in guiding surgical wound closure timing remains unclear. This study evaluates the impact of final preoperative culture results on postoperative outcomes, including flap success, infection rates, and limb salvage.A retrospective review of 344 patients undergoing LE FTT at a single institution was conducted. All patients underwent serial debridement, with final cultures obtained from the final debridement prior to flap reconstruction. Patients were stratified into positive and negative final culture groups. Subgroup analyses assessed the impact of polymicrobial colonization and comorbidity burden (Charlson Comorbidity Index [CCI] >6) on outcomes. Primary outcome was flap infection, defined as any documented clinical concern for infection, including cellulitis, purulent drainage, abscess formation, or initiation of targeted antibiotic therapy.Polymicrobial final cultures were associated with increased infection (p = 0.003) and flap complications (p = 0.041). Among patients with CCI >6, positive final culture was associated with significantly higher infection rates (p = 0.032), but not among those with CCI ≤6. In the total cohort, comparing positive final culture to negative final culture, flap outcomes were similar between groups.Final culture positivity alone does not predict poor outcomes, but polymicrobial cultures and host factors may increase flap infection risk. A risk-stratified approach should guide surgical decision-making, with additional debridement and/or wound bed optimization considered for polymicrobial wounds and polymorbid patients (CCI >6).
Keywords: lower extremity reconstruction; free tissue transfer; qualitative wound; culture